An ab initio kinetics study on 2-methyl-2-butanol oxidation induced by ˙OH radicals. Issue 41 (13th October 2022) - Guo, Shuyan; Zhu, Yuxiang; Zhao, Hao; Zhou, Chong-Wen
Abstract : Rate constants and thermochemical data for H-atom abstraction reactions from 2-methyl-2-butanol by hydroxyl radicals and the subsequent β-scission reactions of the product radicals were calculated. Abstract : High-level ab initio calculations were performed to investigate the kinetics of the important initial steps of 2-methyl-2-butanol (2M2B) oxidation. Hydrogen-atom abstraction reactions by hydroxyl (˙OH) radicals, dehydration reactions of 2M2B molecules, and unimolecular isomerization and decomposition reactions of 2M2B radicals produced by H-atom abstraction were all included in this work. The potential energy surfaces were characterized at the QCISD(T)/CBS//M06-2X/6-311++G(d, p) level of theory. Variational transition state theory (VTST) was employed to calculate the rate coefficients for the H-atom abstraction reactions. It is interesting to note that the hydrogen bond formed in the transition state (TS) in H-atom abstraction reactions, leading to a ring-shaped structure, has a large influence on the electronic energy barriers and rotational–vibrational properties of the TS and thus the rate coefficients. For comparison, rate coefficient calculations were carried out for the same reaction channel by employing different types of TS structures separately, with or without hydrogen bonds. For all the unimolecular reactions studied here, pressure-dependent rate coefficients were obtained through Rice–Ramsperger–Kassel–Marcus/master equation (RRKM/ME) calculations at pressures of 0.01–100 atm. In addition, thermochemical properties at temperatures from 300 to 3000 K for all the species in the title reactions were calculated, which were found to be in good agreement with literature data. The kinetics and thermochemical data calculated in this study are important in predicting the combustion properties of 2M2B, which can be used in the combustion kinetic model development of 2M2B oxidation.